Analysis of the Appropriate Bilingual Learning Model Applied to Elementary School Students - Wulandari, Fenita Mei; Tsania, Jihan Zahra; Hapsari, Fitra Hesti; Musyarofah, Devita Ummul; Damayanti, Karina; Cahyani, Yuni Nur; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bilingual education in elementary schools aims to form a generation that is proficient in language and ready to face global competition, but its implementation faces various challenges from the internal side of students and the external environment. This study analyzes effective bilingual learning models through literature studies to improve students' language and academic competencies. This study uses a literature study method with a qualitative descriptive approach to analyze various literature related to the implementation of bilingual learning in Indonesia. The bilingual learning model is a systematic framework that combines two languages in the learning process to improve students' academic and language skills in a balanced way. By understanding the advantages and challenges of various models such as Preview-Review, Submersion, Immersion, and Transitional, teachers can choose the most appropriate approach to support student development at the elementary school level.